Recent advances in the synthesis of conducting polymers from the vapour phase. (May 2017) - Brooke, Robert; Cottis, Philip; Talemi, Pejman; Fabretto, Manrico; Murphy, Peter; Evans, Drew
Abstract: Inherently conducting polymers (ICPs) combine the electrical properties of metals and semiconductors with a polymer's ability to flex and/or stretch. In general, polymers are relatively simple to synthesise, however, ICPs themselves have had limited uptake in consumer devices. This lack of uptake is in part related to the insolubility of many ICPs in common industrial solvents, and hence methods to manufacture them in a usable form have been problematic. Vapour phase polymerisation (VPP) is one method that provides a convenient route to producing thin films of both soluble and insoluble ICPs, and nanocomposites thereof. In this critical review the VPP process will be discussed from the fundamental viewpoint of the proposed polymerisation mechanism and the parameters affecting polymer growth for a range of different monomers (thiophene, 3-hexylthiophene, pyrrole, 3, 4-ethylenedioxythiophene, etc .). Looking forward into the future, new areas of polymer design and fabrication using VPP will be discussed, such as the enhancement of ICPs through additives, and next generation device fabrication based upon VPP ICPs.